PHYSICAL FITNESS OF STUDENTS OF DIFFERENT SOCIAL AND ECONOMICAL LEVEL FROM RIO DE JANEIRO (Fiep Bulletin - online, 2014)
The aim of this study was analyze the physical fitness of the male students of public (PuS) and private (PrS) school from Rio de Janeiro. The social and economical level were determinated according to their school: public school (low level) and private (high level). Participated of these study 103 male students with age between 10 and 15 years, 47 students of public schools (12.45 1.50 years) and 56 (12.55 1.09 years) of private schools from Rio de Janeiro. Were obtained the height and total body mass to characterize the sample and the motor tests had been used to analyze the physical fitness (Eurofit): flamingo balance, tapping test of Grafic 1: seat and reach test (distance, cm) arms, sit and reach, standing broad jump, hand grip test, abdominal test, bent arm hang, velocity shuttle run and endurance shuttle run. For the statistics analysis was realized the Excel (2003) adopting the t-Student test non-pareated for the comparisons between groups (p = 0,05). It was observed that the groups don't differ for the variable: chronological age, total body mass and height (without significantly differences between the groups), a similar physical development between the analyzed groups was identified. About the tests of motor ability, significantly differences had been found only for the seat and reach test (p=0.02) and the reply time test (ruler) (p=0.02), both with favorable values to PrS group. Pupils of PrS had presented only bigger reach (flexibility of the hip, back and posterior muscles of the inferior members) and better time of reply to the visual stimulation of that of the pupils of the PuS. The social and economical condition didn't promote evident morphologic difference between the groups.
Keywords: adolescents; physical fitness and social; economical levels